INFLUENCE OF DRAGON FRUIT PEEL (Hylocereus polyrhizus) JUICE THROUGH DRINKING WATER ON THE PHYSICAL COMPOSITION OF BALI CHICKEN CARCASSES - N. P. E. A., Pradnyawati; Oka, A. A.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika, 2024)
This study was targeted at observing the impact of administering dragon fruit peel juice through drinking water on the physical composition of male Bali duck carcasses which was carried out in Banjar Tengah Gulingan, Badung Regency, Mengwi District, for 8 weeks. This study used the RAL/Completely Randomized Design (RAL) method which included 5 replications and 4 actions with each replication including 3 ducks. The actions given were that the ducks were given drinking water without dragon fruit skin juice through drinking water (P0), the ducks were given 6% of the juice in the action (P1), the ducks were given 8% of the juice in the action (P2), and for those with 10% of the juice in the action (P3) . For observation, the variables include carcass weight, slaughter weight, meat percentage, carcass percentage, fat & bones including skin. The results of the study showed that male Bali ducks given 6%, 8%, 10% dragon fruit peel juice via drinking water had slaughter weights of 1197g (P0); 1277g(P1); 1224g(P2) and 1194g(P3), carcass weight 688.8g(P0); 705.4g(P1); 684.8g(P2); 657.6g(P3), carcass percentage 57.83%(P0), 55.16%(P1); 56.13%(P2); 55.05%(P3), bone percentage 32.36%(P0); 31.54%(P1), 32.65%(P2); 35.61%(P3), percentage of skin including fat 22.43%(P0); 21.73%(P1); 20.68%(P2); 18.31%(P3) and statistically not significant (P>0.05) but significantly different (P<0.05) in the percentage of meat 45.00%(P0); 46.38%(P1), 47.23%(P2); 46.34%(P3). The conclusion is that if you use 6%, 8%, 10% dragon fruit skin juice from drinking water, it does not affect carcass weight, slaughter weight, percentage of fat bones & carcasses, including skin, but can increase the meat percentage of male Bali ducks.